Bank Debt in Europe : 'Are Funding Models Broken' - Le Lesle, Vanessa (IMF Working Papers; Working Paper ;, 2012)
The crisis in Europe has underscored the vulnerability of European bank funding models compared to international peers. This paper studies the drivers behind this fragility and examines the future of bank funding, primarily wholesale, in Europe. We argue that cyclical and structural factors have altered the structure, cost, and composition of funding for European banks. The paper discusses the consequences of shifting funding patterns and investor preferences and presents possible policy options and bank actions to enhance European bank funding models' robustness.